2005
DOI: 10.1111/j.1651-2227.2005.tb02079.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte membrane acetylcholinesterase, Na+, K+‐ATPase and Mg2+‐ATPase activities in patients with classical galactosaemia

Abstract: (a) AChE, Na+,K+-ATPase and Mg2+-ATPase activities were determined to be decreased in poorly controlled patients with classical galactosaemia. (b) The enzyme activities were inversely correlated with the Gal-1-P blood levels. (c) Since Na+,K+-ATPase in the erythrocyte membranes is the isomer of Na+,K+-ATPase distributed in many tissues and in the brain, evaluation of the enzyme activity in the erythrocytes could be a useful peripheral marker of Gal-1-P toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Therefore, it is likely that hydroxyl radicals may be active species primarily responsible for the oxidative reduction of the PON 1/Aryl in in vivo system (group B). This suggestion is supported by our previous in vitro ( Karikas et al, 1999;Tsakiris and Schulpis, 2000) and in vivo studies (Schulpis et al, 2002;Tsakiris et al, 2005) on another esterase: we reported that low TAS levels decreased both rat brain acetylcholinesterase activity and the erythrocyte membrane acetylcholinesterase activity in patients with classical phenylketonuria (Schulpis et al, 2002) and in those with classical galactosemia 'off diet' (Tsakiris et al, 2005). The enzyme activities were restored to normal when the patients adhered to their diet and their TAS levels were remarkably increased.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, it is likely that hydroxyl radicals may be active species primarily responsible for the oxidative reduction of the PON 1/Aryl in in vivo system (group B). This suggestion is supported by our previous in vitro ( Karikas et al, 1999;Tsakiris and Schulpis, 2000) and in vivo studies (Schulpis et al, 2002;Tsakiris et al, 2005) on another esterase: we reported that low TAS levels decreased both rat brain acetylcholinesterase activity and the erythrocyte membrane acetylcholinesterase activity in patients with classical phenylketonuria (Schulpis et al, 2002) and in those with classical galactosemia 'off diet' (Tsakiris et al, 2005). The enzyme activities were restored to normal when the patients adhered to their diet and their TAS levels were remarkably increased.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, Gal‐1‐P was found to inhibit (–70%) pure human AChE 5 . Similarly, in a very recent study, we found the activity of the erythrocyte AChE to be decreased in poorly controlled patients with classical galactosaemia 6 . The enzyme activity was restored nearly to normal when the patients were put on their special diet.…”
Section: Introductionsupporting
confidence: 74%
“…Finally, we cannot exclude the possibility that high Gal‐1‐P levels might lower the enzyme activities as found in our previous in vitro 4,5 and in vivo studies 6 on another esterase: high Gal‐1‐P levels decreased both AChE activity in rat brain as well as the erythrocyte membrane AChE activity in patients with classical galactosaemia ‘off diet’ 6 and pure human AChE 5 . We suggest that both low TAS indirectly and high serum Gal‐1‐P levels may reduce directly PON1/aryl activities in poorly controlled galactosaemic patients.…”
Section: Discussionmentioning
confidence: 77%
“…Along these lines of evidence, it seems likely that GME could enhance mitochondrial functions, by scavenging free radicals and increase the reduced forms of antioxidants such as GSH and ascorbate that might play roles as potent neuroprotective agents. It has been reported that GME provides direct intracellular availability of GSH (Anderson and Meister, 1989) and this GSH further restored the Na + K + ‐ATPase activity in aged rat brain (Tsakiris et al, 2005).…”
Section: Methodsmentioning
confidence: 95%